2021
DOI: 10.1126/sciimmunol.abe2749
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of mature dendritic cells, T H 2A, and Tc2 cells characterize clinically resolved atopic dermatitis under IL-4Rα blockade

Abstract: Therapeutic options for autoimmune diseases typically consist of broad and targeted immunosuppressive agents. However, sustained clinical benefit is rarely achieved, as the disease phenotype usually returns after cessation of treatment. To better understand tissue-resident immune memory in human disease, we investigated patients with atopic dermatitis (AD) who underwent short-term or long-term treatment with the IL-4Rα blocker dupilumab. Using multi-omics profiling with single-cell RNA sequencing and multiplex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
78
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(94 citation statements)
references
References 93 publications
6
78
0
3
Order By: Relevance
“…Likewise, withdrawal of dupilumab at an early phase is not recommended. Recently, Bangert et al revealed specific immune cell populations, mature dendritic cells, TH2A, and Tc2 cells, that persisted for up to one year after clinical amelioration obtained by dupilumab while being absent from healthy controls J o u r n a l P r e -p r o o f (Bangert et al, 2021). Their data suggest that it takes more than one year for treatment with dupilumab to bring immunological remission even after having achieved clinical amelioration.…”
Section: -2 Efficacy Of Dupilumab By Ethnic Subgroupmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, withdrawal of dupilumab at an early phase is not recommended. Recently, Bangert et al revealed specific immune cell populations, mature dendritic cells, TH2A, and Tc2 cells, that persisted for up to one year after clinical amelioration obtained by dupilumab while being absent from healthy controls J o u r n a l P r e -p r o o f (Bangert et al, 2021). Their data suggest that it takes more than one year for treatment with dupilumab to bring immunological remission even after having achieved clinical amelioration.…”
Section: -2 Efficacy Of Dupilumab By Ethnic Subgroupmentioning
confidence: 99%
“…Likewise, withdrawal of dupilumab at an early phase is not recommended. Recently, Bangert et al. (2021) revealed specific immune cell populations, mature dendritic cells, TH2A, and Tc2 cells, that persisted for up to 1 year after clinical amelioration obtained by dupilumab while being absent from healthy controls.…”
Section: Efficacy and Safety Of Dupilumab For Ad In Clinical Trialsmentioning
confidence: 99%
“…Function of DCs is controlled mainly by stimuli and environmental context, and we can harness this to induce activating or tolerogenic immune responses (17). Therefore, when DCs are targeted with vaccines for either immunity or tolerance, it may be important to filter out beneficial subsets, but it is equally important to provide the right combination of triggers for DCs in order to shape a T cell activating or tolerizing phenotype (43)(44)(45).…”
Section: Subsets For Anti-cancer and Tolerogenic Immunomodulationmentioning
confidence: 99%
“…On the contrary, the study further confirms the insensitivity of T H 2 cells towards GCs in allergic sensitization and inflammation ( 65 ). Especially the persistence of a T H 2 subset, which displays an inflammatory memory phenotype in non-lesioned AD skin, was suggested to play a major role in the recurrence of AD conditions in patients treated with the monoclonal anti-IL-4Rα antibody dupilumab ( 66 ).…”
Section: Tissue-immune Regulation and Interorgan Crosstalkmentioning
confidence: 99%